EVALUASI DAMPAK SOSIAL EKONOMI DALAM PENGEMBANGAN WISATA GOA SEPLAWAN DI KABUPATEN PURWOREJO - Rina Ade Saputri; Hardi Warsono (Journal of Public Policy and Management Review, 2017)
The development of Goa Seplawan tourism is part of the growth of local tourism in Purworejo District. In its implementation, this activity has an impact on the community and local government of Purworejo Regency. The impact of Goa Seplawan tourism development in Purworejo Regency is social and economic impact. The purpose of this study is to analyze the socio-economic impacts of the tourism development of Goa Seplawan in Purworejo District, to analyze the factors influencing socio-economic impacts in the development of Goa Seplawan tourism in Purworejo Regency and to analyze the business Created by the government to minimize the negative impact Tourism development of Goa Seplawan. This study uses the evaluation indicators of effectiveness, adequacy, equity, responsiveness, and accuracy. This research uses descriptive qualitative type with informant that is Head of Tourism Destination Development, Institutional Development and Development Section and Development of Tourism Office, and community around Goa Seplawan. The result of this research is that the people and government of Purworejo Regency do not receive social and economic impact. The people and government of Purworejo Regency only received two good categories of evaluation namely effectiveness and adequacy.